2021
DOI: 10.1111/nmo.14287
|View full text |Cite
|
Sign up to set email alerts
|

Bile Acid Diarrhea in Adults and Adolescents

Abstract: Background Bile acids are central to enterohepatic signaling pathways activated through natural receptors, farnesoid X receptor [FXR mediates synthesis of fibroblast growth factor‐19 (FGF‐19)], and G protein‐coupled bile acid receptor 1 (GPBAR1, also known as TGR5). Although bile acid diarrhea (BAD) is more commonly encountered in ileal resection or disease, there is evidence documenting “idiopathic” BAD in about 20% of adolescents and 30% of adults presenting with chronic, non‐bloody diarrhea often attributed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 80 publications
0
15
0
Order By: Relevance
“…The main secondary bile acids are lithocholic acid, deoxycholic acid and ursodeoxycholic acid. In the colon, bile acids cause increased secretion, increased mucosal permeability and stimulate motility (eg, high amplitude colonic contractions) 17. BAD affects both adolescents and adults 17 18…”
Section: Update On Pathophysiology Of Ibs and Its Diagnosismentioning
confidence: 99%
“…The main secondary bile acids are lithocholic acid, deoxycholic acid and ursodeoxycholic acid. In the colon, bile acids cause increased secretion, increased mucosal permeability and stimulate motility (eg, high amplitude colonic contractions) 17. BAD affects both adolescents and adults 17 18…”
Section: Update On Pathophysiology Of Ibs and Its Diagnosismentioning
confidence: 99%
“…Diagnosis of bile acid diarrhea is made on selenium homotaurocholic acid test (SeHCAT), which is not available in some countries. 49 Third,…”
Section: Discussionmentioning
confidence: 99%
“…We examined the data of included studies in our meta‐analysis, and only three studies provided the data for celiac disease making it insufficient for pooling. Diagnosis of bile acid diarrhea is made on selenium homotaurocholic acid test (SeHCAT), which is not available in some countries 49 . Third , diagnostic evaluation of IBS patients prior to colonoscopy was not standardized among clinical centers, and request to colonoscopy may vary at the discretion of referral physicians, which may cause a selection bias.…”
Section: Discussionmentioning
confidence: 99%
“…The BASs are also proven to be efficacious in the treatment of chronic diarrhea due to the malabsorption of BAs/BSs, often termed as bile acid diarrhea (BAD). Studies had shown that patients with post-ileocecal resection experience a reduction in stool frequency and had an improvement in consistency of stool on a specific dose of cholestyramine per day; additionally, the urgency of defecation, perianal soreness, and flatus were also decreased in most cases. In patients with mild diarrhea, bile acid sequestrants provide symptomatic relief by lowering the concentration of free bile acids in the colon. , Figure represents the list of off label use of BASs reported in various literature and research guidelines.…”
Section: Polymeric Bass In the Market: Mechanism Indications Advantag...mentioning
confidence: 99%